A Novel Glycyrrhetinic Acid-Modified Oxaliplatin Liposome for Liver-Targeting and in vitro/vivo Evaluation [Retraction] - Chen J; Jiang H; Wu Y; Li Y; Gao Y (Dove Medical Press, 2022)
Chen J, Jiang H, Wu Y, Li Y, Gao Y. Drug Des Devel Ther. 2015;9:2265–2275. The Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Concerns were raised regarding the alleged duplication of images in Figure 5 with the same images from other unrelated articles. Specifically, Figure 5A, Liver appears to have been duplicated with the same image from Figure 4Ba from Li & Gong (https://doi.org/10.2147/DDDT.S113670). Figures 5A and 5B Lung appear to have been duplicated with the same images from Figures 4Aa and 4Ab, respectively, in Li & Gong (https://doi.org/10.2147/DDDT.S113670). Figures 5A, 5B and 5C Kidney appear to have been duplicated with the same images from Figures 5A, 5B and 5C, Kidney, respectively in Zhou et al, 2018 (https://doi.org/10.2147/DDDT.S146925). The authors did not respond to our queries and no explanation for the alleged image duplication was provided. The Editor requested to retract the article and the authors were notified of this. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.